GREEN MINING EXTRACTS ZINC, NICKEL AND COBALT FROM PLANTS/ REVIEW ARTICLE - Shahla hussien huno; Dr.Huda Farooq Zaki; Dr. Reyam Naji Ajmi; Estabraq Mohammed Ati (European Journal of Humanities and Educational Advancements, 2024)
The demand for metals is constantly increasing as a result of economic and urban growth and population growth, as they are a major component of modern technologies and industries. However, the aspects of mining activity currently used have negative impacts on the environment, human health and existence. Will scientists in the future be able to discover innovative technology to use synthetic biology and engineer plants and stimulate them so that they are able to produce minerals sustainably? Soil contains many minerals that plants use as nutrients throughout their life cycle for their growth among the minerals necessary for this growth cycle are: phosphorus, potassium, calcium, sulfur, magnesium, copper, zinc, iron, manganese, molybdenum, boron, nickel, cadmium, and cobalt.